Effects of Therapy on Rate of Absorption of Calcium from Gut in Disorders of Calcium Homoeostasis. Issue 5926 (3rd August 1974) - Reeve, J.; Hesp, R.; Veall, N.
Abstract : A development of the double-tracer calcium absorption test, in which a function is derived for single-passage entry rate from the gut with time, has been assessed in various disorders of calcium homoeostasis. Single tests are diagnostically useful in calcium malabsorption but because of the wide spectrum of normal values a single test can only moderately enhance the accuracy of the diagnosis of hypercalcaemic states made primarily by other methods. On the other hand serial studies in the same subject can be much more informative because the test is normally highly reproducible if conditions are unchanged. Serial studies play an important part in assessing the efficacy of established methods of treatment in disorders of calcium homoeostasis and should be particularly helpful in studying the effects of new forms of therapy on the absorption process.